The course of multidrug-resistant pulmonary tuberculosis in HIV-infected people with COVID-19 - Raznatovska, O. M.; Myronchuk, Yu. V.; Shalmin, O. S.; Fedorets, A. V. (Zaporozhye Medical Journal, 2022)
Aim. To analyze the course of multidrug-resistant tuberculosis (MDR-TB) in HIV-infected people, depending on the time to COVID-19 diagnosis, using the example of clinical cases from our own observation. Materials and methods. The article presents 3 clinical cases of our own observation of MDR-TB in HIV-infected persons depending on the time to COVID-19 diagnosis in patients, who were treated in the Pulmonary Tuberculosis Department No. 2, clinical base of the Department of Tuberculosis and Pulmonology ZSMU – Municipal non-profit enterprise “Zaporizhzhia Regional Phthisiopulmonology Clinical Medical and Diagnostic Center” of Zaporizhzhia Regional Council. Results. In clinical case 1, in an HIV-infected patient, MDR TB was detected after COVID-19. This clinical case has shown that after mild and treated COVID-19, even on the background of severe immunosuppression, but with AMBT and ART timely prescribed, MDR-TB in the patient had a favorable course with positive dynamics. In clinical case 2, in an HIV-infected patient, MDR-TB was detected concomitantly with COVID-19. The clinical case indicated that the patient received all 3 therapies for MDR-TB, HIV and COVID-19 in full and on time. In contrast to clinical case 1, the patient was diagnosed with a more severe process that required a longer period of treatment, although it was effective. In clinical case 3, an HIV-infected patient with COVID-19 was diagnosed after 5 months of MDR-TB treatment. Against this background, there was culture positivity. But after prescription of appropriate COVID-19 treatment against the background of AMBT and ART, positive dynamics and culture negativity were determined. All 3 patients completed antimycobacterial therapy of MDR-TB with results – recovery. Conclusions. Regardless of the HIV infection duration with underlying severe immunosuppression (<200 CD4 lymphocyte cells) and the time to COVID-19 diagnosis (before, during or after the diagnosis of MDR-TB) on the background of timely therapy of MDR-TB, HIV and COVID-19, positive results can be achieved while saving the lives of patients.